Assessment of perceived stress and association with sleep quality and attributed stressors among 1st-year medical students: A cross-sectional study from Karwar, Karnataka, India - Clevin Rashmi Rebello; Prasad Budri Kallingappa; Preethi G Hegde (Tzu Chi Medical Journal)
Objectives: The objective is to study the extent of perceived stress among 1st-year medical students using the Perceived Stress Scale-14 (PSS-14) and its association with sleep quality as assessed by the Pittsburgh Sleep Quality Index (PSQI) and attributed stressors. Materials and Methods: A cross-sectional study was conducted of 121 1st-year medical students at Karwar Institute of Medical Sciences, Karwar, Karnataka, India. The extent of their stress was assessed using the PSS-14 and their sleep quality was assessed using the PSQI. Graded stress exerted by the attributed stressors was also assessed. Results: A total of 33.8% of participants had perceived stress scores of >28. Among academic stressors, performance in examinations (34.7%), lack of time for recreation (30.6%), curriculum (24.8%), and frequency of examinations (24.8%) were the highest rated stressors. Quality of food in the mess (50.4%) and lack of entertainment in the institution (39.7%) were the highest rated psychosocial stressors. There was a positive correlation between the PSS-14 scores and various academic stressors and the global PSQI score. Conclusion: First-year medical students reported a high level of stress, including academic and psychosocial stressors. Effective changes in the curriculum and living conditions can reduce the level of stress among these students.